Application of Moving Bed Biofilm Reactor (MBBR) and Integrated Fixed Activated Sludge (IFAS) for Biological River Water Purification System: A Short Review - Lariyah M.S.; Mohiyaden H.A.; Hayder G.; Hussein A.; Basri H.; Sabri A.F.; Noh M.N. (Institute of Physics Publishing, 2023)
Bioreactors; Effluents; Purification; Water treatment plants; Activated sludge; Biological process; Bioreactor system; Conventional methods; Current treatments; Emerging technologies; Moving bed biofilm reactors; Treatment process; Biological water treatment; activated sludge; biofilm; effluent; operations technology; pollutant removal; purification; river water; urban area; water treatment